ANALISIS HUKUM TERHADAP ASAS LEX SPECIALIS DEROGAT LEGI GENERALI PASAL 36 UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG JAMINAN FIDUSIA DALAM KASUS PENGGELAPAN - Elsa Maharani; Firman Wijaya (Jurnal Hukum Adigama, 2020)
In the judiciary in Indonesia there are often criminal violations of fiduciary guarantees, one of which is regulated in Article 36 of Law Number 42 Year 1999 concerning Fiduciary Guarantees. That Article has a relation on the basis of the principle of lex specialis derogat legi generali with Article 372 of the Criminal Code (KUHP). But as a lex specialis, fiduciary guarantees are often ruled out for application, as in the Purworejo District Court ruling number: 15 / Pid.Sus / 2015 / Pn.PWR. Then how is the application of article 36 of the Fiduciary Guarantee Law as lex specialis of Article 372 of the Criminal Code in the case in the decision? In this study, normative legal research methods will be used. The results of the research show that there was a mistake made by the Judge in making decisions related to the decision and the Prosecutor in prosecuting. This can be seen from the way the Judge and Prosecutor in examining the legal facts that exist. As a legal scholar, judges and prosecutors should pay more attention to the principles of applicable law and examine legal facts better.